Jerzle food products refining of soybean oil extraction of soybean protein - Evangelista, Romel S.; Lee, Edmund P.; Zagala, Jose. (Diliman, Quezon City College of Engineering, 1967)
Capacity: 60,000 lbs/day of crude oil -- Land area: 3 hectares -- Total fixed capital investment: 5,781,325 -- Operating cost at maximum production: 3,876,024 -- Annual sales at maximum production: 5,120,000 -- Pay-off time: 4 years -- Maximum annual rate of production: 16,000,000 lbs -- Break-even point: 31% -- Shutdown point: 12.5% -- % return on investment: 17.1%
Plant design.
Typescript
Submitted in partial fulfillment of the requirements in ChE 62 Chemical Engineering Plant Design.
Keywords: Factories -- Design and construction; Soybean processing plants; Soy oil; Soy proteins